Trade Relations between Poland and Asian Economies from 2006 to 2008 - Pawlas, Iwona (Relacje handlowe Polski z krajami Azjatyckimi w latach 2006-2008, 2010)
A rise in the intensity of trade, capital and technological relations between subjects from different parts of the world can be seen as both a sign of and a result of internationalization and globalization. Asian economies represent an important group of subjects of the processes. Poland is an active participant of internationalization and globalization as well. Poland's involvement in the world economy has resulted from political, economic and social changes introduced in late 1980s and the beginning of the 1990s. In the case of the Polish economy, however, a strong regionalization of relations is observed. Especially Poland's trade relations concentrate in Europe. Obviously it does not mean the absence of such cooperation between Poland and Asian economies. The paper aims at analyzing the development of trade relations between Poland and Asian partners from 2006 to 2008.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; s. 316-325 Nr 126
Keywords: exports; imports; Asia; China; revealed comparative advantage; intra-industry trade